Behavior of gold-doped silicon substrate under small- and large-RF signal. (June 2020) - Nabet, Massinissa; Rack, Martin; Hashim, Nur Zatil Ismah; de Groot, C.H. (Kees); Raskin, Jean-Pierre
Abstract: In this paper, small- and large-signal performances of passive devices integrated on high-resistivity, trap-rich and gold-doped silicon wafers are presented and compared through measurements and simulations. The gold-doped silicon substrate was produced starting from standard silicon having a nominal resistivity of 56 Ω · cm. We show that the gold-doped substrate presents high effective resistivity and low losses suitable for RF applications. This has been demonstrated by measuring coplanar waveguides, crosstalk, inductors and band pass filter where we observed similar performances for small-signal measurements compared with trap-rich substrate. Large-signal measurements of gold-doped substrates show 60 dBm lower harmonic distortion than high-resistivity substrates, and 10 dB lower than trap-rich substrate at 0 V DC bias. However, a large DC bias dependence on the harmonic distortion induced by the gold-doped substrate is observed. This unexpected behavior is explained using the Fermi level localization in the silicon bandgap for the different DC bias conditions.